Isolation demand from carbapenemase-producing Enterobacteriaceae screening strategies based on a West London hospital network. Issue 2 (October 2016) - Vella, V.; Moore, L.S.P.; Robotham, J.V.; Davies, F.; Birgand, G.J.C.; Otter, J.A.; Brannigan, E.; Dyakova, E.; Knight, G.M.; Mookerjee, S.; Holmes, A.H.
Summary: Objective: To estimate the isolation demands arising from high-risk specialty-based screening for carbapenemase-producing Enterobacteriaceae (CPE), and the potential fraction of CPE burden detected. Methods: Clinical specialty groups from three London hospitals were ranked by incidence of carbapenem resistance among Escherichia coli and Klebsiella spp. Contact precaution bed-days were estimated for three screening strategies: Strategy 1, 'circulation science and renal medicine'; Strategy 2, Strategy 1 plus 'specialist services'; and Strategy 3, Strategy 2 plus 'private patients'. Isolation bed occupancy rates and potential CPE detection rates were estimated. Results: Of 99, 105 admissions to the three hospitals in Financial Year 2014/15, Strategies 1, 2 and 3 would have screened 4371 (4.4%), 7482 (7.6%), and 13, 542 (13.7%) patients, respectively. The specialties' isolation bed occupancy rates varied between 3% and 696% depending on strategy, number of consecutive tests, and whether or not pre-emptive isolation had been applied. Expected detection rates of the potential CPE burden in the hospital network would have varied between 17.1% and 47.5%. Conclusions: High-risk specialty-based screening has the potential to detect nearly half of the potential CPE burden, and would be more pragmatic than patient-level risk-factor-based screening. Pre-emptive isolation increases isolation requirements substantially. CPE screening strategies need to balance risk and resources.